Cultural Studies’ Approach as a Methodological Basis of Modern Pedagogical Education - Aryabkina, Irina; Medvedeva, Irina (Տիգրան Մեծ)
The subject of this article is the methodological features of the cultural studies‟ approach as the foundation, the basis of modern teacher education. The article deals with various types of culture; the need for understanding at a new his-torical stage characterized by global environmental and social challenges, the role of the teacher as a carrier of Culture in the modern school, the application of various aspects of the cultural studies‟ approach to building individual cultural trajectories of students in the process of modern teacher education is noted. Based on the consideration of the views of scientists from various scientific schools regarding possible solutions to the above very complex and urgent tasks, the significance of art and creative activity in the professional and pedagogical development of a modern teacher is revealed.The result of the theoretical and empirical study of this issue by the authors of the article was the development and implementation on the basis of pedagogical universities of the Russian Federation of a parametric model of professional and pedagogical training of future teachers for the organization of culturally appropriate pedagogical interaction with school-children. The goals, objectives and fundamental principles of introducing this model into the educational process are briefly disclosed in this article.
Keywords: Methodology; Philosophy of education